Effects of Dilution Rate on Fermentation Characteristics of Feeds With Different Carbohydrate Composition Incubated in the Rumen Simulation Technique (RUSITEC) - Pfau, Friederike; Hünerberg, Martin; Südekum, Karl-Heinz; Breves, Gerhard; Clauss, Marcus; Hummel, Jürgen (Frontiers in Animal Science, 2021)
This study investigated the impact of carbohydrate source and fluid passage rate (dilution rate) on ruminal fermentation characteristics and microbial crude protein (MCP) formation. Three commonly used feeds (barley grain [BG], beet pulp [BP], and soybean hulls [SBH]), which differ considerably in their carbohydrate composition, were incubated together with a mixture of grass hay and rapeseed meal in two identical Rusitec apparatuses (each 6 vessels). Differences in fluid passage rate were simulated by infusing artificial saliva at two different rates (1.5% [low] and 3.0% [high] of fermenter volume per h). This resulted in six treatments (tested in 3 runs): BGhigh, BGlow, BPhigh, BPlow, SBHhigh and SBHlow. The system was adapted for 7 d, followed by 4 d of sampling. Production of MCP (mg/g degraded organic matter [dOM]; estimated by 15N analysis) was greater with high dilution rate (DL; p < 0.001) and was higher for SBH compared to both BG and BP (p < 0.001). High DL reduced OM degradability (OMD) compared to low DL (p < 0.001), whereas incubation of BG resulted in higher OMD compared to SBH (p < 0.002). Acetate:propionate ratio decreased in response to high DL (p < 0.001). Total gas and methane production (both /d and /g dOM) were lower with high DL (p < 0.001). In our study increasing liquid passage rate showed the potential to increase MCP and decrease methane production simultaneously. Results encourage further studies investigating these effects on the rumen microbial population.